The geography of urban environmental protection in Slovenia: The case of Ljubljana - Aleš Smrekar; Mateja Breg Valjavec; Katarina Polajnar Horvat; Jernej Tiran (Acta Geographica Slovenica, 2020)
This paper uses findings from sustainability studies to present the development of environmental urban geography in Slovenia in recent decades. Modern European cities, of which Ljubljana is no exception, depart significantly from sustainable development concepts. Compared to other similar cities, Ljubljana has an effective green space system, which its residents also perceive as offering a better-quality living environment. The major, poorly addressed problems are primarily inherited issues, such as gravel pits, illegal dumping sites, and unregulated gardens in suburbanized water protection areas on which residents depend. These, however, show a large gap between claimed and actual environmental awareness.